Paleoproterozoic Metamorphism of the Archean Tuntsa Suite, Northern Fennoscandian Shield - Hölttä, Pentti; Kivisaari, Tiia; Huhma, Hannu; Rollinson, Gavyn; Kurhila, Matti; Butcher, Alan R. (Minerals, 2024)
The Tuntsa Suite is a polymetamorphic Archean complex mainly consisting of metasedimentary gneisses. At least two strong metamorphic events can be distinguished in the area. The first took place at high temperatures in the Neoarchean at around 2.70–2.64 Ga, indicated by migmatisation and U-Pb ages of metamorphic zircon. During the Paleoproterozoic, metasedimentary gneisses were penetratively deformed and recrystallized under medium pressures producing staurolite, kyanite and garnet-bearing mineral assemblages. The suggested Paleoproterozoic PT path was clockwise where the temperature and pressure first increased to 540–550 °C and 6 kbar, crystallizing high Ca/low Mg garnet cores. The mineral compositions show that commonly garnet core was not in chemical equilibrium with staurolite but crystallized earlier, although garnet-staurolite-kyanite assemblages are common. The temperature and pressure increased to c. 650 °C and 8 kbars where staurolite and kyanite coexist. This was followed by decompression down to c. 550–600 °C and 3–4 kbars, shown by andalusite crystallization and cordierite formed in the breakdown of staurolite and biotite + kyanite. The observed garnet zoning where Mg increases and Ca decreases from the core to the rim was developed with both increasing and decreasing pressure, depending on the effective bulk composition. The U-Pb and Sm-Nd age determinations for monazite and garnet show that the Paleoproterozoic metamorphic cycle took place at 1.84–1.79 Ga, related with thrusting of the Lapland granulites onto the adjacent terranes and subsequent exhumation.